Mix Code in Seller Transaction Communication and “Otak-Otak” Buyers on The Six Seas River East Bintan District, Bintan Regency - Dini Prastiani; Abdul Malik; Asri Lolita³ (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research discusses the code mixing found in speech between sellers and buyers of otak-otak in Sungai Enam Laut, East Bintan District, Bintan Regency. The aim of this research is to describe forms of code mixing in speech between sellers and buyers of Otak-Otak Sungai Enam Laut, East Bintan District, Bintan Regency. The method used is qualitative descriptive qualitative. The data in this research are in the form of code mixing. The data collection technique used to obtain research data is the observation method technique. This observation technique is supported by using documentation techniques, listening techniques, note-taking techniques and recording techniques. The results of this research are that there are forms of code mixing in the form of 1) word insertion, 2) phrase insertion, 3) word repetition insertion, and 4) clause insertion.